2019
DOI: 10.1111/1462-2920.14561
|View full text |Cite
|
Sign up to set email alerts
|

Increased algicidal activity of Aeromonas veronii in response to Microcystis aeruginosa: interspecies crosstalk and secondary metabolites synergism

Abstract: Summary Toxic Microcystis spp. blooms constitute a serious threat to water quality worldwide. Aeromonas veronii was isolated from Microcystis sp. colonies collected in Lake Kinneret. Spent Aeromonas media inhibits the growth of Microcystis aeruginosa MGK isolated from Lake Kinneret. The inhibition was much stronger when Aeromonas growth medium contained spent media from MGK suggesting that Aeromonas recognized its presence and produced secondary metabolites that inhibit Microcystis growth. Fractionations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 78 publications
(93 reference statements)
0
15
0
Order By: Relevance
“…A. veronii is widely distributed and can be isolated from diseased aquatic animals and aquatic environments (17)(18)(19) in various countries such as Poland (20), Mexico (21), and Japan (22). The pathogen can cause human biliary sepsis and diarrhea in clinical practice (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…A. veronii is widely distributed and can be isolated from diseased aquatic animals and aquatic environments (17)(18)(19) in various countries such as Poland (20), Mexico (21), and Japan (22). The pathogen can cause human biliary sepsis and diarrhea in clinical practice (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be examined whether this is also the case in Microcystis cells, armoured with a large array of secondary metabolites the role of most of which is yet to be revealed. Also, the role of secondary metabolites produced by bacteria associated with Microcystis colonies (Weiss et al ., ; Weiss et al ., ) is yet to be clarified.…”
Section: Resultsmentioning
confidence: 99%
“…Intensification of toxic cyanobacterial blooms such as Microcystis aeruginosa (hereafter Microcystis ) in the last decade is a matter of growing concern due to the formation and release of toxins to the water bodies (Sukenik et al ., ; Paerl and Otten, ; Paerl and Otten, ; Hadas et al ., ; Harke et al ., ; Otten et al ., ; Huisman et al ., ). In many aquatic ecosystems, Microcystis strains form colonies that float on the water surface forming surface scums and producing a large array of secondary metabolites The biological roles of many of the secondary metabolites are not fully understood, although their involvement in extracellular and intracellular functions were proposed (see Rantala et al ., ; Sedmak and Elersek, ; Schatz et al ., ; Zilliges et al ., ; Kaplan et al ., ; Holland and Kinnear, ; Rzymski et al ., ; Makower et al ., ; Meissner et al ., ; Harke et al ., ; Kaplan et al ., ; Pearson et al ., ; Schuurmans et al ., ; Weiss et al ., and references therein). Among the secondary metabolites produced, the intensively investigated microcystins are known to inhibit certain eukaryotic protein phosphatases and thus they are harmful to humans, wildlife and livestock (Huisman et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the minute quantities of 1 – 3 , they were tested only for the growth inhibition of M. aeuroginosa strain MGK by cell counting, but they were found to be inactive. The only active metabolite we isolated from the culture medium was lumichrome [5]. The abovementioned metabolites, 1 – 3 , are most probably derived from the enzymatic transformation of primary metabolites rather than products of secondary metabolism by special biosynthetic genes.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study we showed interspecies interactions between the non-pathogenic Aeromonas veronii and a toxic cyanobacterium in a fresh body lake, implicating secondary metabolites in the cross-talk between these organisms. Enhanced lumichrome production by A. veronii in response to the presence of culture media from the toxic cyanobacterium Microcystis aeruginosa strain MGK and inhibition of MGK growth by applications of pure lumichrome implicated this metabolite in the cross-talk between these two microorganisms [5]. Analysis of its genome (accession no.…”
Section: Introductionmentioning
confidence: 99%